Development and Evaluation of Clinical Efficacy of Intraocular Lens Fixation after Cataract Phacoemulsification, Complicated by Capsular Lenticular Disruption - A. A. Kozhukhov; D. O. Kapranov; I. G. Ovechkin; N. I. Ovechkin (Oftalʹmologiâ, 2018)
Рurpose. Evaluation of the clinical efficacy of the original procedure for fixing the posterior chamber intraocular lens (IOL) after phacoemulsification of cataracts (FEC), complicated by the violation of capsular lens support.Patients and Methods. 194 patients were examined after FEC,  complicated by a capsular lenticular impairment. They were divided  into 3 groups. In the main group (OG, 64 eyes) the IOL was sutured  with an original technique, fundamentally different method, there  nodes formed at the ends of the filaments were fixed in the layers of the cornea. In 2 controls groups, there the traditional IOL under  the scleral flap (K1, 68 eyes) was performed and the IOL was  attached to the iris (K2, 62 eyes). A comprehensive examination of  the patients’ vision state included an evaluation of clinical, functional and subjective indicators.Results. The lowest total probability of postoperative complications development was noted in OG (6.4%) compared to K2 and K1  (16.0–17.7%). The overall probability of changing the positions of  the IOL in the exhaust gas is 6.4%, which is significantly lower than  in the K2 (9.6%) and K1 (14.6%) groups. The developed method in  comparison with the traditional methods of fixation provides a higher level of patient’s quality of life (by 10.2–11.7%, p < 0.05)  and functional indicators associated with the brightness and contrast sensitivity of the eye.The conclusion. The developed technique provides, in comparison with the traditional, a higher level of safety and functionality of IOL fixation.